PENAMPILAN GENOTIPE SOM JAWA Talinumpaniculatum Jacq. (Gaertn.) PADA GERERASI M2 - Poerba, Yuyu Suryasari (Research Center for Biology-Indonesian Institute of Sciences, 2004)
Javasom [Talinum paniculatum Jacq. (Gaertn.] is one of popular vegetable plants with potential medicinal properties.The plant root is often used as a substitute for ginseng (Panax ginseng L.), and the leaves are used as a vegetable and as a substitute for purslane (Portulaca olaraeae L.).An effort to improve genetic quality of the plant was made through induced mutation with ethyl methane sulphonate (EMS).A variety of EMS dosages (0, 0.3%, 0.6%, 0.9%, 1.2%, 1.5% and 1.8%) were applied to javasom seeds to induce mutation for 24 hours at room temperature. A population of the first and second generation after mutagen treatment (M, and M2,respectively) was established and observed at vegetative and generative stages. At M, generation, plant growth was suppressed and plant yield was decreased.Chimeras and chlorophyll mutation were observed in every EMS-treatment level, which was indicated that mutation was induced in the plant. Lethal-dosage (LD-50) of EMS was at 1.2%-1.5%. M, population were recovered and showed variation in all parameters observed. High genetic variation coefficients were found in most of plant characters observed.All parameters have a medium to high heritability, which indicated that all parameter observed were relatively easily inherited.However, all genotypes are subjected to be evaluated in the next generation in their performance stability.